BALANCED SCORECARD - INSTRUMENT OF STRATEGIC PLANNING - Maria SILIVESTRU (Revista Română de Statistică, 2012)
Balanced Scorecard (BSC) is a system of management and an instrument of strategic planning, spread within business and industry, in state public institutions, as well as in non-profit institutions. BSC improves external and internal communication and also monitors the performance of an organization starting from its strategic objectives.In the past, BSC played the part of performance measurement. Lateron, the BSC concept evolved and fully became an instrument of strategic planning.This article tries to achieve a translation of the concepts into official statistics, identifying concrete measures to be done and measured by an organization. It is useful for the execution of the organization strategy.It is estimated that the new modern approach of strategic management, respectively BSC, allows the national institutes of statistics to clarify the vision and strategy and translated them into actions.